Hydration during exercise in warm, humid conditions: Effect of a caffeinated sports drink - Millard-Stafford, M. L.; Cureton, K. J.; Wingo, J. E.; Trilk, J.; Warren, G. L.; Buyckx, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Caffeine is regarded as a diuretic despite evidence that hydration is not impaired with habitual ingestion. The purpose of this study was to determine whether a caffeinated sports drink impairs fluid delivery and hydration during exercise in warm, humid conditions (28.5 °C, 60% relative humidity). Sixteen cyclists completed 3 trials: placebo (P), carbohydrate-electrolyte (CE), and caffeinated (195 mg/L) sports drink (CAF+CE). Subjects cycled for 120 min at 60-75%VO2max followed by 15 min of maximal-effort cycling. Heart rate and rectal temperature were similar until the final 15 min, when these responses and exercise intensity were higher with CAF+CE than with CE and P. Sweat rate, urine output, plasma- volume losses, serum electrolytes, and blood deuterium-oxide accumulation were not different. Serum osmolality was higher with CAF+CE vs. P but not CE. The authors conclude that CAF+CE appears as rapidly in blood as CE and maintains hydration and sustains cardiovascular and thermoregulatory function as well as CE during exercise in a warm, humid environment.